Studi Potensi Interaksi Antibiotik Dengan Obat Lain Pada Peresepan Pasien Pneumonia Di Intensive Care Unit - Yeni Farida (Jurnal Farmasi Indonesia, 2022)
Pneumonia is one of the most common acute lower respiratory tract infection that causes morbidity and mortality. Most of it is caused by bacteria. Antibiotics is the main therapy of bacterial infection cases. Concomitant use of antibiotics and other drugs may risk harmful interaction. This study aimed to determine the potential antibiotic drug interactions and their effects on the patient's condition based on clinical data and laboratory. A retrospective study were conducted in ICU, NICU and PICU. Medical records of pneumonia patients in 2016 who met the inclusion criteria, including patients diagnosed with pneumonia with co-morbidities, received antibiotic therapy at least 3 days, and had bacterial culture data. Drug interactions were analyzed using Stockley's Drug Interaction, Drug Interaction Fact, and Medscape then calculated the percentage potential of interaction, phase, and significance of interactions. The results showed that among 28 patient there were 17 types of drugs which potentially cause drug interactions in patients with pneumonia based on literature. Percentage of pharmacokinetics drug interaction was 80%; pharmacodynamics was 20%. Potential drug interactions on metabolism phase were 44%; excretion phase was 36%. The potential effect of drug interactions was major (10%), moderate (80%) and minor (10%). Potentially, most of drugs interact in the metabolic phase with moderate significance. The high drug interaction potential was gentamycin and furosemide with moderate significance about 16%.